2023
DOI: 10.1002/advs.202306457
|View full text |Cite
|
Sign up to set email alerts
|

Dying to Defend: Neutrophil Death Pathways and their Implications in Immunity

Haiyue Tu,
Haoyu Ren,
Junjie Jiang
et al.

Abstract: Neutrophils, accounting for ≈70% of human peripheral leukocytes, are key cells countering bacterial and fungal infections. Neutrophil homeostasis involves a balance between cell maturation, migration, aging, and eventual death. Neutrophils undergo different death pathways depending on their interactions with microbes and external environmental cues. Neutrophil death has significant physiological implications and leads to distinct immunological outcomes. This review discusses the multifarious neutrophil death p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 202 publications
(355 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, a total of 289 lactylation sites were detected among 181 proteins that underwent lactylation modifications in Kupffer cells [ 38 ]. Pyroptosis is a regulated inflammatory modality of cellular demise distinguished by cellular enlargement, lysis, and the liberation of intracellular constituents [ 39 ]. Moreover, we revealed that Sal B reduced the expression of H3K18la sites and the downstream NLRP3/caspase-1/IL-1β inflammatory pathway in M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a total of 289 lactylation sites were detected among 181 proteins that underwent lactylation modifications in Kupffer cells [ 38 ]. Pyroptosis is a regulated inflammatory modality of cellular demise distinguished by cellular enlargement, lysis, and the liberation of intracellular constituents [ 39 ]. Moreover, we revealed that Sal B reduced the expression of H3K18la sites and the downstream NLRP3/caspase-1/IL-1β inflammatory pathway in M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The lower neutrophil percentage in osteopenic, sarcopenic, and osteosarcopenic patients may be a reactive response influenced by various factors, including age. Pro-inflammatory cytokines, such as IL6 and IL1β, contribute significantly to the phenomenon of inflammation, both during sarcopenia and osteoporosis, also enhancing PGE2 [ 46 , 47 ]. PGE2, associated with osteoclastogenesis, contributes to bone resorption in osteoporosis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%